2018
DOI: 10.1042/cs20180167
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits inflammatory signals in the gut by controlling AMPK and p38 MAP kinase activation

Abstract: Metformin, a hypoglycemic drug used for treatment of type 2 diabetes, regulates inflammatory pathways. By using several models of intestinal inflammation, we examined whether metformin exerts anti-inflammatory effects and investigated the basic mechanism by which metformin blocks pathologic signals. Colitic mice given metformin exhibited less colonic inflammation and increased expression of active AMP-activated protein kinase, a mediator of the metabolic effects of metformin, in both epithelial and lamina prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 43 publications
3
47
0
2
Order By: Relevance
“…For example, activated macrophages and T-helper 17 cell have increased glucose uptake and glycolysis; conversely, anti-inflammatory cells, such as M2 macrophages, regulatory T cells, have lower glycolytic rates and higher levels of oxidative metabolism. AMPK activation creates a pseudo-starving state that can promote oxidative metabolism and inhibits inflammation through many signaling networks, such as nuclear factor κB and mitogen-activated protein kinases (MAPK) signaling pathway ( O’Neill and Hardie, 2013 ; Song et al, 2015 ; Peixoto et al, 2017 ; Di Fusco et al, 2018 ). Hence, AMPK is a crucial regulator of these metabolic dysfunction responses in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, activated macrophages and T-helper 17 cell have increased glucose uptake and glycolysis; conversely, anti-inflammatory cells, such as M2 macrophages, regulatory T cells, have lower glycolytic rates and higher levels of oxidative metabolism. AMPK activation creates a pseudo-starving state that can promote oxidative metabolism and inhibits inflammation through many signaling networks, such as nuclear factor κB and mitogen-activated protein kinases (MAPK) signaling pathway ( O’Neill and Hardie, 2013 ; Song et al, 2015 ; Peixoto et al, 2017 ; Di Fusco et al, 2018 ). Hence, AMPK is a crucial regulator of these metabolic dysfunction responses in immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…26,96 Inflammation directly disrupts the assembly of apical junctions and thus increases epithelial permeability. 97 In addition, inflammation activates Wingless and Int (Wnt)/β-catenin signaling, which promotes epithelial proliferation but inhibits differentiation, thus impairing epithelial barrier formation. 96,98 AMPK activation triggers cell cycle arrest, 99,100 consistent with the repressive roles of AMPK in epithelial proliferation and promotion of differentiation.…”
Section: Ampk In Epithelial Differentiation Inflammation and Barriermentioning
confidence: 99%
“…Cha et al have shown that metformin reduces the stability and membrane localization of programmed death-ligand 1 (PD-L1) and contributes to the enhancement of cytotoxic T lymphocyte (CTL) activity against cancer cells [ 28 ]. Metformin also exerts anti-inflammatory effects [ 29 , 30 ]. It was recently reported that these effects might be related to the alteration of gut microbiota [ 31 ].…”
Section: Immunomodulatory Effects Of Drugs Used For Treating Commomentioning
confidence: 99%